Genetic testing of UGT1A1 in the diagnosis of Gilbert syndrome: The discovery of seven novel variants in the Chinese population. Issue 7 (14th April 2022) - Gu, Leilei; Han, Yue; Zhang, Donghua; Gong, Qiming; Zhang, Xinxin
Abstract: Background: Genetic testing of UGT1A1 was used to facilitate the diagnosis of Gilbert syndrome, and analyze the distribution features of pathogenic variants in the Chinese population. Methods: DNA was extracted from whole blood samples of patients with unconjugated hyperbilirubinemia, and sequencing of the UGT1A1 gene was performed after PCR amplification. After alignment with reference sequences, the known pathogenic variants were identified, the variant spectrum was analyzed, and the pathogenicity of novel variants was predicted using online mutation prediction tools. Results: A total of 117 patients were confirmed with Gilbert syndrome by UGT1A1 genetic diagnosis, where the most common pathogenic variants included promoter A(TA)7 TAA insertion and p.Gly71Arg missense variant. Following novel variants were also identified: p.Ala61Gly, p.Tyr67Phe, p.Leu166Alafs*16, p.Arg240Lys, p.Ser306Phe, p.Arg341Gln, and p.Glu424* variants. Conclusions: Genetic testing of UGT1A1 in clinical practices could facilitate confirming Gilbert syndrome and performing differential diagnosis. The pathogenic variant spectrum in the Chinese population was similar to other Asian populations. The novel pathogenic variants identified in this study require further investigation. Abstract : We identified 7 novel variants, which expanded the spectrum of UGT1A1 variants, and provided new references for relevant genetic diagnosis. We furthermore investigated the features of the variant spectrum in Chinese patients with Gilbert syndrome.